Exploratory and confirmatory analysis of the family parenting styles scale (ECF-29) in high school students - Estrada Alomía, Erika (2017)
The purpose of this research is to analyze the psychometric properties of the scale of family parenting styles (ECF-29), supported by structural equations, a multivariate statistical analysis to compare models that propose causal relationships between variables. The sample consisted of 609 students of public educational institutions, from the 1st to 5th year of high school, and whose ages were between 11 and 18 years, from the districs of Los Olivos and Independencia. There were selected by intentional sampling and the estimation model used is the maximum plausibility. The results revealed the covariances, variances and factorial saturations as adequate; likewise, the styles are estimated according to the absolute adjustment indexes (GFI, AGFI>0.95, RMSEA and RMR<0.05) and increase or comparative values (TLI, NFI and IFC>=0.95) with optimal values corroborate the pertinence of accepting the model of four factors or patterns explaining behavior in parents. It is concluded that through the path analysis developed with the dimensions of the scale, we can approximate an adequate adjustment to the proposed model.